Sesarmid crabs (brachuyra: grapsoidea: sesarmidae) in West Peninsular Malaysia and Brunei Bay Mangroves: Historical review and updates on ecology and biodiversity at community and species levels / Laura Ribero - Laura, Ribero (2019)
Sesarmid crabs (Brachyura: Grapsoidea: Sesarmidae) are dominant components of the mangrove macrofauna worldwide. In particular, South East Asia hosts one of the highest diversity of sesarmid species, living in intertidal and supratidal wetlands. However, despite their well documented ecological role as primary consumers and ecosystem engineers, information on ecology and biology of many species is scarce, and their taxonomy is constantly being revised, with several new species described in the past few years. On the other hand, mangroves and other wetlands are being rapidly converted to other uses. The sesarmid communities of the Malay Peninsula (Peninsular Malaysia and Singapore) and northern Borneo have been investigated in several studies. However, a comprehensive review on the available information in this area is not available. The main objectives of this project are (i) to historically review the state of knowledge on sesarmid crabs in Peninsular Malaysia, Singapore and northern Borneo, (ii) to provide a synopsis of the Malaysian sesarmid species, containing any published information available for each species, (iii) to update the local checklists, through field surveys in several localities, and (iv) to provide new information on the ecology and distribution of the local species, through ecological analyses. First, a comprehensive literature research was conducted, considering any work ever published on each sesarmid species recorded from Malaysia. A historical review and a synopsis of the species were presented, providing a detailed source of information for researchers and conservationists in this region, and a biodiversity guide for educational purposes. Surveys were conducted in several mangrove forests along the West coast of Peninsular Malaysia (Kuala Selangor, Tanjung Tuan, Langkawi, Pulau Besar, Pulau Kukup and Pulau Merambong). Sesarmid and other grapsoid crabs were collected to obtain species inventories for each site, most of which have not been investigated before. Several environmental variables at different scales were also recorded (type of substrate, forest type and size, and insularity). Ecological analyses investigated the spatial distribution of species relatively to the recorded variables. The results highlighted differences in communities living in different sites and environments, with few common species able to cope with different conditions, and numerous non-common species which were found only in a few study sites. Field surveys were conducted also in the Brunei Bay (Borneo), to update existing checklists from Bornean peritidal systems, and to investigate the community structure, diversity, and distribution. Several new records were reported for Borneo and Brunei Darussalam. The specimens were collected through a time- and area-based sampling method, in several sites, hosting different types of peritidal systems (mangroves, Nypa forests, peat swamps, disturbed grass meadows). A few variables were chosen to describe the ecological conditions (salinity, substrate, type of vegetation, distance from the mangrove seaward fringe). Assemblages of different ecosystems differed in terms of both species richness and taxonomic composition. High intertidal zones hosted peculiar communities, differentiated both among themselves, and between them and lower intertidal communities. These results highlighted the importance of preserving different types of coastal wetlands, maintaining the intertidal transition to avoid loss of diversity in these communities.